Development of the First Potential Nonpeptidic Positron Emission Tomography Tracer for the Imaging of CCR2 Receptors - Wagner, Stefan; de Moura Gatti, Fernando; Silva, Daniel G.; Ortiz Zacarias, Natalia V.; Zweemer, Annelien J.M.; Hermann, Sven; de Maria, Monica; Koch, Michael; Weiss, Christina; Schepmann, Dirk; Heitman, Laura H.; Tschammer, Nuska; et al. (ChemMedChem, 2020)
Herein we report the design and synthesis of a series of highly selective CCR2 antagonists as 18F-labeled PET tracers. The derivatives were evaluated extensively for their off-target profile at 48 different targets. The most potent and selective candidate was applied in vivo in a biodistribution study, demonstrating a promising profile for further preclinical development. This compound represents the first potential nonpeptidic PET tracer for the imaging of CCR2 receptors.
CRIS-Team Scopus Importer:2020-12-04
Keywords: CCR2; CCR5 antagonists; chemokine receptors; molecular imaging; PET; radiolabeling; TAK-779